Two new records of the genus Termitomyces from North India - Kumari, Babita; Atri, N S; Upadhyay, R C (Mushroom Research, 2012)
Two agarics namely, Termitomyces reticulatus and Termitomyces schimperi have been illustrated and described, of which T. reticulatus is a new record for India where as T. schimperi is being described for the first time from North India. The above agarics were collected from North India during monsoon season.